Pengaruh Metode Eksperimen Terhadap Hasil Belajar Ilmu Pengetahuan Alam Siswa Kelas V SD Inpres Maroanging Gowa - Nurjannah Nurjannah; Nasrah Nasrah; Nurul Magfirah (Journal on Education, 2023)
The Effect of Experimental Methods on Science Learning Outcomes of Grade V Students at SD Inpres Maroanging Gowa. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, University of Muhammadiyah Makassar. Advisor I Nasrah and advisor II Nurul Magfirah. The purpose of this study was to determine the effect of the Experimental Method on Science Learning Outcomes of Class V SD Inpres Maroanging Gowa. This research is a type of pre-experimental research with a research design using one group pretest-posttest design through a quantitative approach. This design made two measurements, the first (pretest) and the second measurement (posttest). The sample in this study was class V SD Inpres Maroanging Gowa, as many as 28 students. The results showed that the average student pretest result was 51.07 in the low category, then the experimental method was applied to the learning process so that the posttest results of students achieved an average score of 76.25 in the medium category. The N-Gain analysis shows that the average normalized gain is 0.54 in the medium category. Based on the hypothesis test using the paired samples test, the value of Sig. (2-tailed) of 0.000 <0.05. This means that H0 is rejected and H1 is accepted, which means that there is an effect of the use of the experimental method on science learning outcomes in fifth grade students at SD Inpres Maroanging Gowa on heat transfer material.